Efficacy of intranasal cetamine for pain reduction in adults in emergency situations: a systematic literature review - Mafalda Antunes; Maria Francisca Gomes; Marta Matos; Vilma Vieira; Fernando Gama (Millenium)
Introduction: Pain is one of the most prevalent clinical manifestations in emergency settings. Traditionally, opiates have been widely used to control it, but in recent decades there has been a significant change in analgesic approaches, with growing interest in non-opiate alternatives. These include ketamine, whose pharmacological profile has aroused interest due to its analgesic efficacy, especially in situations of intense acute pain.